Africa's fuelwood footprint and the biome-level impacts of tree harvest - Tredennick, Andrew T., author; Galvin, Kathleen, advisor; Hanan, Niall P., advisor; Coughenour, Michael, committee member; Leisz, Stephen, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: alternative stable states; fuelwood; modeling; savanna; Africa